BARRIERS TO MARKET ENTRY AND STRATEGIES FOR SUCCESS: A STUDY ON SMALL AND MEDIUM ENTERPRISES (SMES) IN GHANA AND TANZANIA - Mwamba, Katarina (UIN Sunan Gunung Djati Bandung, 2024)
Small and Medium Enterprises (SMEs) play a pivotal role in the economic development of emerging economies, yet they face substantial barriers to market entry that can impede their growth and sustainability. This study aims to analyze the major barriers to market entry encountered by SMEs in Ghana and Tanzania and explore the strategic approaches adopted to overcome these challenges. Utilizing a comprehensive literature review, this research synthesizes existing knowledge on entry barriers such as regulatory constraints, access to finance, market competition, and infrastructure deficits. The findings indicate that while both countries face similar obstacles, the intensity and impact of these barriers vary due to distinct economic and policy environments. Moreover, the study identifies successful strategies, including innovation, networking, and capacity building, that SMEs employ to navigate these challenges. By highlighting these barriers and strategies, this study contributes to a deeper understanding of the SME landscape in Ghana and Tanzania, offering insights for policymakers and practitioners to foster a more supportive business environment. The research emphasizes the need for targeted policy interventions to reduce entry barriers and enhance the competitive capabilities of SMEs. Future research should further investigate the dynamic interactions between these barriers and strategies across different sectors.